Rubella vaccination during the preconception period or in pregnancy and perinatal and fetal outcomes - Ergenoğlu, Ahmet Mete; Yeniel, Ahmet Özgür; Yıldırım, Nuri; Kazandı, Mert; Akercan, Fuat; Sağol, Sermet (The Turkish Journal of Pediatrics, 2012)
The rubella vaccine is contraindicated in pregnancy. Between July and August 2009, the Turkish Republic Ministry of Health implemented a vaccine program to eradicate rubella in women in the reproductive period. In this program, many pregnant women were also vaccinated inadvertently. In this study, 62 pregnant women applied to our clinic who were vaccinated either during pregnancy or within one month before the last menstrual period. Seventeen of them were followed until the end of the pregnancy by fetal echocardiography and detailed ultrasonography. Rubella immunoglobulin (Ig) M and IgG antibodies were studied in the cord blood obtained at birth. All fetuses were examined by a pediatrician, an ophthalmologist and a pediatric cardiologist. A hearing test was also performed on all neonates. No signs of congenital rubella syndrome could be found.